Prediksi Perilaku Aliran di Belokan Saluran menggunakan Particle Swarm Optimization - Setiawan, Hery Teguh; Adipradana, Arrizka Asyriati (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
Hydraulically, the flow behavior in straight and turning lines is different because it is influenced by geometric factors and other related hydraulic parameters. The hydraulic behavior of straight and turning lines has been widely studied by means of theoretical, experimental and numerical approaches. The theoretical approach is very limited and still leaves many questions, while the experimental approach requires large research costs, so that the numerical approach through computation can be used as a reliable alternative research as long as it is based on a theoretical basis and valid experimental data. The purpose of this research is to analyze and predict the flow behavior of channel bends using Particle Swarm Optimization (PSO). Ã‚Â optimization algorithm. The results obtained indicate that the PSO can be relied upon in modeling the fluid flow velocity at the channel bends with an average error percentage of 8% compared to the measured data.